NILAI CBR PADA STABILISASI TANAH DENGAN SEMEN JALAN BUDI UTOMO UNIB DEPAN - mawardi mawardi; Makmun R. Razali; Olandri Wijaya (Universitas Bengkulu, 2019)
CBR value research on soil stabilization with cement in the Budi Utomo UNIB Depan for influence soil properties and soil CBR original value after stabilisation with cement. Geotechnical Lab Testing was conducted at the Faculty of Engineering UNIB. Test laboratory soil properties include: density, water content, sieve analysis, Proctor standard test, Atterberg limits, and experimental value of CBR (California Bearing Ratio) laboratory. Stabilization soft soil made with cement with the addition of cement content of 0%, 2%, 4%, 8% and 12%. Based on test results propeties soil and the value of laboratory CBR. CBR maximum value at additioning cement content of 12%, the CBR value an increase of 144.21%, of the original soil conditions, dry density increase 3.85%, of the original soil, optimum moisture content decrease 13.75% of the original soil, PI value decresel 50.42% of the original soil, the value of specific gravity (Gs) increse 1.93% of the original soil. Stabilization with cement increasing the value of CBR, which means it will also boost the stability of the soil and will also increase the soil bearing capacity (qu). The increase in soil stabilization and soil bearing capacity proportional to the increase in the value of CBR amounted to 144.21%, this is due to the presence of silica, clay and limestone contained in the hydraulic cement is a binder.